2006
DOI: 10.1103/revmodphys.78.373
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-induced states in conventional and unconventional superconductors

Abstract: We review recent developments in our understanding of how impurities influence the electronic states in the bulk of superconductors. Our focus is on the quasi-localized states in the vicinity of impurity sites in conventional and unconventional superconductors and our goal is to provide a unified framework for their description. The non-magnetic impurity resonances in unconventional superconductors are directly related to the Yu-Shiba-Rusinov states around magnetic impurities in conventional s-wave systems. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

64
1,501
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,289 publications
(1,571 citation statements)
references
References 347 publications
(437 reference statements)
64
1,501
6
Order By: Relevance
“…[137]. Conventional s-wave superconductors are well-known to be robust against non-magnetic disorder.…”
Section: Impurity Effectsmentioning
confidence: 99%
“…[137]. Conventional s-wave superconductors are well-known to be robust against non-magnetic disorder.…”
Section: Impurity Effectsmentioning
confidence: 99%
“…Thus impurity states in graphene distinguish strongly from their counterparts in usual semiconductors, where the DOS in the valence and conduction bands are very different and impurity levels lie generally far away from the middle of the gap. Impurity effects on the electronic structure of twodimensional systems with Dirac spectrum were investigated in detail in connection with the problem of hightemperature superconductivity in copper-oxide compounds, and STM visualization of the order parameter around impurities is one of the most straightforward evidences of the d-wave pairing in these systems [14]. For the case of a strong enough impurity potential, the formation of quasilocalized electron states in the pseudogap around the Dirac point is expected [14], whereas a weak potential will not lead to the formation of quasilocalized states at all.…”
mentioning
confidence: 99%
“…Moreover, following the argument in Refs. [11,12] we expect sharp features in the response ∂ 2 I/∂V 2 ∝ ∂δN (r, ω)/∂ω at the inelastic resonances ω = ±ω 0 for low temperatures. These expected features of the response to the inelastic scattering are verified in Fig.…”
mentioning
confidence: 86%
“…Theoretically, it has been shown that vibrational modes in a arXiv:0811.1782v2 [cond-mat.mes-hall] 20 Apr 2010 molecular structure adsorbed on a metallic surface would be measurable by means of IETS in a narrow energy range around the vibrational mode [11,12]. Moreover, the inelastic scattering generates Friedel oscillations in the local surface density of states (DOS), thus enabling spatial imaging of the inelastic signatures.…”
mentioning
confidence: 99%